(untitled) (LICERE - Revista do Programa de Pós-graduação Interdisciplinar em Estudos do Lazer, 2012)
This paper aims to discuss public policies in sport and leisure in the counties that comprise the Northwest Region / RS. The collected data show that in most municipalities are organized calendars of competitive sports events in a few sports, almost exclusively for men. Just a few cities in the region have the section in charge of being the manager in sport and leisure, as well, present shortage in skilled human resources to perform the function. It is understood that is necessary the organization by the public agency in charge of being the manager and articulator of community participation in the definition of the public policies about sport and leisure.